Fast Tracking RLS Adaptation Algorithms of the Second-Order Volterra Digital Filters - Vasko, J.; Kocur, D. (Radioengineering Society, 1995)
Two new fast tracking exponentially weighted conventional recursive least-squares (RLS) algorithms of adaptation of the adaptive Volterra filters (AVF) for time-varying systems are presented. The new algorithms are based on a modification of a priciple of variable forgetting factor with unity zone [1]. Their additional computational complexity due to the forgetting factor adaptation is negligible compared to that of conventional RLS algorithms. The performance properties of the proposed algorithms are verified via computer experiments.
Keywords: volterra filters; adaptive filters; TLS algorithms; forgetting factor adaptation